WORKING WIFE'S NAFKAH FAMILY LAW PERSPECTIVE INDONESIAN ISLAM - Nelli, Jumni (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
This research aims to analyze the income position of working wives in Islamic family law in Indonesia. In classical jurisprudence, the husband has the obligation to pay his wife's maintenance, based on the rules of separation of assets in marriage. Meanwhile in Indonesia, maintenance is determined by the husband, with the implementation of joint property. This proof was carried out by examining books related to this study. Qualitative descriptive analysis was carried out after complete data was obtained. The results of this research explain that there is no text that expressly prohibits wives from working and there is no text that explicitly states that wives must work with their husband's permission. In classical jurisprudence, a wife's income from work is the husband's obligation, as is the case in Indonesia. However, it is not in line with the implementation of joint property, so it brings ambiguous legal treatment. The implementation of joint property in marriage has an impact on the implementation of all obligations in the household being carried out jointly, including the obligation to fulfill maintenance.